Support for the Health System in Times of Crisis: From Macro to Micro - Jorda Vargas, Liliana; Vouillat, Silvia; Parra, Ricardo A. (Revista del Hospital Italiano de Buenos Aires, 2025)
The health system in a sanitary crisis, from the macro to the micro, requires the insertion and commitment of the institutions. In the post-pandemic period, health policies coexist and fluctuate. By the way, we must be clear about the changing social determinants and not deprive us of essential public health functions. Those mark us along the way towards organizational resilience. The right to health and the protection of vulnerable populations will always remain intrinsic to individuals within society. It is more powerful in times of crisis. We must find the space for institutional management to ease the burden on the health system and enhance resource efficiency. It requires internal analysis, strategic planning, and application of patient-centered care. The population, health professionals, and institutions are responsible for supporting personal actions and institutional policies within the macro health system during a health crisis.